Analisis Sikap Wisatawan Dalam Menciptakan Pengelolaan Berkelanjutan (Studi Pada Pantai Mesra Gunungkidul) - Pramukti, Regina Tyas; Sulistyo, Agung; Soeroso, Amiluhur (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
Several beaches do not maintain their existence, so interest in visiting them is low. This condition differs from Mesra Beach, which experienced a growth in visitors. To support its existence, managers must pay attention to visitors' needs. This situation is an effort to create sustainable tourism through visitor satisfaction. This research aims to determine visitors' attitudes toward Mesra Beach. This research uses mixed research methods as an exploratory effort. The Fishbein attitude model is used as a data analysis technique. Data collection uses questionnaires and interviews. Questionnaires were distributed to 384 respondents, while open interviews were conducted to explore the questionnaire results. The attributes used in this research include beach cleanliness, natural beauty, accessibility, facilities, and aesthetic photo spots. The research results explain that visitors' attitudes towards Mesra Beach are positive (92,600). This value is in the correct position (cut of the point) between the agree and strongly agree ranges. The aesthetic photo spot attribute obtained the highest attitude value (22.081). Meanwhile, the complete facilities attribute obtained the lowest attitude value (9.694). Managers can maintain the best attributes and improve the quality of attributes that obtain the opposite value. This way, Pantai Mesra can maintain its existence and formulate further policies